Pengaruh Globalisasi Terhadap Penggunaan Bahasa Indonesia - Adrian Muhammad Yusuf (Jurnal Mahasiswa Kreatif, 2023)
The rapidly growing influences of globalization unknowingly already mushed in the commynity. This is evidenced by the use of language Indonesian that is shifted with the use of traditional foreign languages. Technology development through modern communication tools become one of the important things in communicating in the globalization. The use of communication tools is usually utilized in daily life, both parents and children. This research uses qualitative descriptive research. The subject of this research is a community aged 7-12 years. The used is a poll given to respondents. Test of normality and homogenity test is used as test hypotheses.The research shows that there is an influence of globalization on the use of language Indonesian. It is seen from the tcount> ttable is 6,675 > 2,10092.